The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2967/jnumed.117.193946
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of PET Response Combined with Baseline Metabolic Tumor Volume in Peripheral T-Cell Lymphoma Patients

Abstract: Peripheral T-cell lymphoma (PTCL) is a heterogeneous group of aggressive non-Hodgkin lymphomas with poor outcomes on current therapy. We investigated whether response assessed with PET/CT combined with baseline total metabolic tumor volume (TMTV) could detect early relapse or refractory disease. From 7 European centers, 140 patients with nodal PTCL who underwent baseline PET/CT were selected. Forty-three had interim PET (iPET) performed after 2 cycles (iPET2), 95 had iPET performed after 3 or 4 cycles (iPET3/4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 29 publications
8
53
1
3
Order By: Relevance
“…Additionally, the use of SUV metrics as prognostic factors when pooling data from several PET systems would be affected by reconstruction inconsistencies. Finally, the delineation of metabolically active tumor volume, which is increasingly being used as a prognosticator in lymphoma patients (19,20), is strongly affected by the use of advanced reconstruction algorithms (21). For these reasons, it seems preferable to pursue ongoing harmonization efforts with programs such as EARL or QIBA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of SUV metrics as prognostic factors when pooling data from several PET systems would be affected by reconstruction inconsistencies. Finally, the delineation of metabolically active tumor volume, which is increasingly being used as a prognosticator in lymphoma patients (19,20), is strongly affected by the use of advanced reconstruction algorithms (21). For these reasons, it seems preferable to pursue ongoing harmonization efforts with programs such as EARL or QIBA.…”
Section: Discussionmentioning
confidence: 99%
“…Eine zunehmende Anzahl von Studien berichtet von der prognostischen Aussagekraft prätherapeutischer oder (seltener) Interim-Response (semi)quantitativer [18F]FDG-PET-Parameter, welche neben SUV-Werten auch metabolisches Tumorvolumen (MTV) und totale Glykolyse im Lymphomgewebe (TLG, Produkt aus MTV und mittlerem SUV) umfassen. Die bisherigen Ergebnisse lassen auf eine Anwendbarkeit über ein breites Spektrum verschiedener Lymphomsubtypen schließen, welches u. a. Hodgkin-Lymphome, DLBCL, follikuläre Lymphome, MALT-Lymphome und T-Zell-Lymphome umfasst [32][33][34][35][36][37]. Diese prognostische Aussagekraft, welche in den meisten Fällen auf die Vorhersage des progressionsfreien Überlebens (PFS, "progression-free survival") oder Gesamtüberlebens (OS, "overall survival") abzielt, ließ sich für Patienten unter verschiedenen Therapien nachweisen.…”
Section: Quantitative Parameter Und Prognostikunclassified
“…Notably, many previous studies have also shown that pretherapeutic SUVs, metabolic tumor volumes (MTV), and total lesion glycolysis (TLG) extracted from [ 18 F]FDG‐PET enable outcome prognostication in a variety of histological subtypes, including HL, DLBCL, FL, and also T‐cell lymphomas . In addition, [ 18 F]FDG‐PET has also been evaluated as a tool for risk stratification in clinical trials, and several studies to investigate this topic are still ongoing.…”
Section: Lymphomamentioning
confidence: 99%